PKM memperbaiki alat-alat listrik rumah tangga pada masyarakat di Kecamatan Labakkang Kabupaten Pangkajene dan Kepulauan - Edy Sabara; Sabran Sabran (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Community service activities are carried out to the community of Pattallassang Village, Labakkang District, Pangkajene Regency and the Islands. This service is carried out in the form of training on maintenance and repair of household electrical appliances. The purpose of community service activities is to provide service to the community by providing training on: how to care for household electrical appliances in general, diagnose damage, and repair damage based on diganosa. The material provided in this training activity included: maintenance of household electrical appliances, repair of damage to household electrical appliances, operation of household electrical appliances, and installation of household electrical appliances. Implementation of community service regarding household electrical appliances went smoothly. Community service activities produce results; increased participant's knowledge of the benefits of maintaining electrical equipment, increased participant's knowledge of damage diagnoses, and increased participant's knowledge of correct household electrical appliances repairs.